2016
DOI: 10.19070/2379-1578-1600013
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antioxidant Capacity and Free Radical Scavenging Activity of Milk from Native Cows (Bos Indicus ), Exotic Cows (Bos Taurus ), and Riverine Buffaloes (Bubalus Bubalis ) Across Different Lactation Stages

Abstract: The aim of this study was to evaluate comparative changes in total antioxidant capacity and free radical scavenging activity of milk during lactation in different cattle types and buffaloes. Milk samples from a total of 96 healthy animals of Sahiwal cows (Indian native cattle), Karan Fries cows (Cross-bred), Holstein Frisian cows (exotic cattle) and Murrah buffaloes (Riverine buffaloes) were collected at different lactation stages; early lactation (5-15 days), peak (30-60 days), mid (100-140 days) and late lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…It should be emphasized that fat-soluble vitamins, primarily E and A, are the main antioxidants derived from the fat fraction protecting cells against reactive oxygen species [ 36 , 39 ]. Their activity consists of scavenging organic free radicals and inhibiting lipid peroxidation [ 73 ]. Similarly, Kuczyńska et al [ 65 ] reported an increase in the content of vitamins E and A in milk fat after supplementation with a mixture of oregano, cumin, and rosemary.…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized that fat-soluble vitamins, primarily E and A, are the main antioxidants derived from the fat fraction protecting cells against reactive oxygen species [ 36 , 39 ]. Their activity consists of scavenging organic free radicals and inhibiting lipid peroxidation [ 73 ]. Similarly, Kuczyńska et al [ 65 ] reported an increase in the content of vitamins E and A in milk fat after supplementation with a mixture of oregano, cumin, and rosemary.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Mann et al . [ 36 ] found that during the early and peak stages of lactation, TAC levels were lower in milk from Sahiwal cows (indigenous Indian cattle) than in milk from Karan Fries cows (hybrids). Our results suggest that the immune cells of Brahman × Thai native crossbreed cattle have better antioxidant capacity than those of Brahman cattle, indicating that crossbreed cattle are more resistant to stress responses and oxidative stress than purebred breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamins (soluble in either milk fat or milk serum) and minerals play an essential role as antioxidant factors. The antioxidant capacity of vitamins E (α-tocopherol), A, and C (ascorbic acid) as well as carotenoids is due to their ability to scavenge free radicals (mainly oxygen, hydroxyl, and peroxyl radicals), inhibit lipid peroxidation, and protect DNA from damage [17,18]. Supplementation of milk with ascorbic acid in light-exposed milk enhanced the antioxidant capacity of milk and inhibited the degradation of riboflavin [19].…”
Section: Milk Component With Antioxidant Activities: An Overviewmentioning
confidence: 99%